Lotus seed oligosaccharides at various dosages with prebiotic activity regulate gut microbiota and relieve constipation in mice. (December 2019) - Su, Han; Chen, Jinghao; Miao, Song; Deng, Kaibo; Liu, Jiawen; Zeng, Shaoxiao; Zheng, Baodong; Lu, Xu
Abstract: The aim of this study was to evaluate the effects of lotus seed oligosaccharides (formulation consisting of LSO2, LSO3-1, LSO3-2 and LSO4; relative ratios are 1.107:0.554:0.183:0.443, m/m/m/m) at dosages of 0.42, 0.83 g/d/kg bw and 2.49 g/d/kg bw on the microbiota composition and the propulsion of intestinal contents in the gut of mice. The results showed that fecal water content increased in treated mice; there was less gut microbiota diversity than in other groups; and there was a large number of fauna in the cecum of the mice. At the same time, the number of short-chain fatty acid (SCFA) bacterial producers increased after feeding with oligosaccharides; Lotus seed oligosaccharides (LOS) also enhanced the concentration of SCFAs in the intestine, which also increased the concentration of cytokines in the serum of mice. In conclusion, these findings suggest that LOS or combination with resistant starch has a better effect on relieving constipation. Graphical abstract: Feeding with oligosaccharide-resistant starch complexes has a better effect on beneficial gut microbiota, inhibit pathogenic bacteria, and promote intestinal peristalsis and defecation, resulting in relieving constipation and enhancing intestinal health. Image 1 Highlights: Lotus seed oligosaccharides enhance the proportion of probiotics in gut microbiota. The time of defecation is related to the diet of oligosaccharides. The effects of medium and high doses of oligosaccharides are stronger than those of low doses. Feeding with oligosaccharide-resistant starch complexes has a better effect on beneficial gut microbiota.